Diabetes impact on serum irisin level alongside other biochemical parameters - H. Ahmed, Media; ZM. Al-Abachi, Saba (Medicinski časopis, 2023)
Objective: The goal of the current study was to measure the irisin hormone level as well as certain other biochemical parameters associated with type 2 diabetes (T2D). Methods: A total of 65 type 2 diabetic patients were enrolled in this in this cross-sectional study versus 60 healthy subjects as a control group. The demographic data were recorded, and blood samples were withdrawn from patients and the control group. Serum separated and frozen for subsequent biochemical assays conducted for measured parameters, namely irisin, fasting serum glucose (FBS), insulin, C-peptide, total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), very low-density lipoprotein (VLDL-C) in the patients and control group. A fraction of blood samples were immediately processed for measurement of glycated haemoglobin (HbA1c). Results: There was a significant (p≤0.01) decrease in the irisin concentration in patients with T2D in comparison to the control group. Depending on sex, age and body mass index (BMI), the results have shown a non-significant difference in the irisin level, in patients with T2D or the control group. Conclusion: Irisin could be an additional measured parameter alongside lipid profile and glucose level in diabetic patients reflecting the patient status in term of prognosis or clinical follow-up.
Keywords: Irisin; FNDC5; Diabetes; Lipid profile; C-peptide